THE BEHAVIOR OF GOLD DURING LISTVENITIZATION: EXPERIMENTAL AND THEORETICAL SIMULATION - Likhoidov G.G.; Plyusnina L.P.; Shcheka Z.A. (My University, 2007)
The metasomatic formation of listvenite is widespread in the ophiolite complexes of different ages and interesting for geologists owing to its high gold potential. The listvenites were first described as the product of hydrothermal alteration of dunites and peridotites in the Urals. Later, the gold-bearing listvenites formed during hydrothermal alteration of serpentinites were studied in the ophiolite complexes of the Appalachian region of Quebec, Turkey, and the Ust’-Dep block of the middle Amur region. Listvenites are quartz–carbonate rocks with an admixture of chlorite, fuchsite, talc, chromite, sulfides, and magnetite. The carbonates are mainly ankerite, magnesite, and breinerite. The listvenitization of ultramafic rocks is commonly attributed to the late emplacement of orogenic granitoids that produced chloride–carbon dioxide fluids. The elevated contents of As, Sb, and Hg in listvenites confirm the contribution of granite-related hydrothermal fluids, whereas the presence of Cr, Ni, Co, and Pt attests to the ultramafic protolith.